Structural Functionalism in Rural Primary Education: An Inquiry into the Alleviation of Digital Dilemmas - 郑郑坤芳 (Pacific International Journal, 2024)
This paper thoroughly examines the educational challenges faced by China’s rural primary schools in the modern digital context and suggests solutions based on the structural functionalism theory. The allocation of educational resources in rural primary schools is blatantly unequal under the dual structures of urban and rural areas, and the use of digital teaching also creates the dual issues of system imbalance and incomplete function. This paper, which is based on the structural functionalism theory, explains the challenges that digital education in rural primary schools faces, including a lack of resources, a shortage of skilled teachers, and an imperfect top-level educational design. In light of these challenges, the paper proposes some solutions, including enhancing the creation of digital education resources, enhancing teachers’ capacity for digital teaching, creating and refining the digital management system for rural primary education, and fostering shared values to support the social identity of rural primary education digitization. In order to improve rural primary education in China, close the educational resource gap between urban and rural areas, advance educational equity, and raise the standard of rural primary education, this paper offers a theoretical and practical perspective on the digital transformation of rural primary schools.